The athlete and gut microbiome: Short-chain fatty acids as potential ergogenic aids for exercise and training - Bongiovanni, T.; Yin, M. O. L.; Heaney, L. M. (International Journal of Sports Medicine, 2021)
Short-chain fatty acids (SCFAs) are metabolites produced in the gut via microbial fermentation of dietary fibers referred to as microbiota-accessible carbohydrates (MACs). Acetate, propionate, and butyrate have been observed to regulate host dietary nutrient metabolism, energy balance, and local and systemic immune functions. In vitro and in vivo experiments have shown links between the presence of bacteria-derived SCFAs and host health through the blunting of inflammatory processes, as well as purported protection from the development of illness associated with respiratory infections. This bank of evidence suggests that SCFAs could be beneficial to enhance the athlete`s immunity, as well as act to improve exercise recovery via anti-inflammatory activity and to provide additional energy substrates for exercise performance. However, the mechanistic basis and applied evidence for these relationships in humans have yet to be fully established. In this narrative review, we explore the existing knowledge of SCFA synthesis and the functional importance of the gut microbiome composition to induce SCFA production. Further, changes in gut microbiota associated with exercise and various dietary MACs are described. Finally, we provide suggestions for future research and practical applications, including how these metabolites could be manipulated through dietary fiber intake to optimize immunity and energy metabolism.